Case Report: Clinical and pathological features of a metastasizing malignant mixed epithelial and stromal tumor of the kidney in a Siberian tiger (Panthera tigris altaica) - Švara, Tanja; Gombač, Mitja; Kojc, Nika; Harej, Mojca; Kastelic, Marjan; Kržan, Peter; Dolenšek, Tamara; Kvapil, Pavel (Frontiers in Veterinary Science, 2025)
We describe a case of mixed epithelial and stromal tumor (MEST) of the kidney with widespread metastases in an eight-year-old male Siberian tiger (Panthera tigris altaica) from the ZOO Ljubljana. The tiger presented with hematuria, and after unsuccessful treatment attempts with antibiotics, an ultrasound examination followed by laparotomy was performed. During the laparotomy, a large encapsulated lesion weighing 9.3 kg was found in the location of the left kidney and surgically removed. Histopathological examination of the lesion revealed an encapsulated tumor with a biphasic growth pattern consisting of mesenchymal and epithelial components. Numerous mitoses, hemorrhages, and necrosis were found in the mesenchymal component, which resembled ovarian stroma, leading to the diagnosis of malignant MEST of the kidney. After 3 months, the tiger clinically deteriorated and was euthanized after diagnostic imaging revealed multiple metastases. At necropsy, numerous metastases were found at the site of the previously excised tumor, at the laparotomy scar, in the peritoneum, liver, pancreas, omentum, mesentery, lungs, and sternal lymph nodes. Microscopically, the tumor lesions consisted only of the malignant mesenchymal component. To our knowledge, this is the first report of malignant MEST of the kidney with peritoneal seeding and distant metastases in animals.